Urban planning and citizen participation with Healthy Cities approach (Case Study: Mashhad Emamie neighborhood) - arash sadri; mahmod heidari; arezo bangiyan tabrizi (تحقیقات کاربردی علوم جغرافیایی)
The city health, social and physical environment with all facilities that perform life activities with ease and efficiency makes possible. Urbanization, followed by its specific problems such as environmental degradation, water pollution, air, soil, increase mental illnesses and civil society more than ever threatened. This has led to today's urban design and urban management many challenges in the field of population, housing shortage, pollution and environmental degradation, social conflicts and provision of services and facilities infrastructure is facing. In this regard, the plan to create a healthy city public participation plays an important role in cities. In fact, a healthy city, city to realize a healthy person. The urban design approach and engage in healthy people. This cross-sectional study and data collection instruments and survey was conducted in two ways. According to the results, the neighborhood Shiite index of the five health (social, economic, environmental, health and culture) desirable standards Healthy City away in some areas also need to redesign and greater participation authorities and people in the neighborhood felt. The paper solutions to create healthy city with the participation of the people through the realization of indicators and metrics have reached a healthy city.